A COMPARATIVE STUDY OF TEACHING STRATEGIES USED BY NOVICE AND EXPERIENCED ENGLISH TEACHERS IN SENIOR HIGH SCHOOL - Agda Pinky Ikea Wulandari; Luh Putu Artini; Ni Luh Putu Eka Sulistia Dewi (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2026)
This study aims to compare the teaching strategy preferences between novice and experienced English teachers in one of the Senior High School in Gianyar regency, in the context of the Merdeka Curriculum implementation. This research employed a qualitative descriptive design. The subjects were one novice teacher and one experienced teacher, while the objects were their teaching strategies preferences. The data were collected through observation, in-depth interviews, and teaching strategies checklist. The findings revealed that the novice teacher preferred Project-Based Learning and Cooperative Learning, which foster collaboration, creativity, and active student involvement. Meanwhile, the experienced teacher tended to use Discovery Learning and Integrated Learning, which promote student independence and the integration of cross disciplinary knowledge to deepen understanding. These findings indicate that teaching experience influences the selection of teaching strategies and highlight the importance of ongoing professional development to equip teachers with appropriate pedagogical approaches in alignment with 21st-century education demands.